Protective effect of resveratrol against pembrolizumab-induced hepatotoxicity and neurotoxicity in male rats - Turkmen, Nese B.; Yuce, Hande; Sahin, Yasemin; Taslidere, Asli C.; Ozek, Dilan A.; Unuvar, Songul; Ciftci, Osman (Wiley, 2023)
The present study investigates the effects of resveratrol (RSV) on brain and liver tissues in rats with pembrolizumab (PEMB)-induced toxicity. Obtained for the study were 28 male Sprague-Dawley rats (3-4 months old) which were divided into four groups: Group 1: Control. Group 2: Administered PEMB at 5 mg/kg/day i.p. for a week. Group 3: Administered RSV orally at the dose of 20 mg/kg/day for 30 days by gavage. Group 4: Administered PEMB and RSV at 20 and 5 mg/kg/day RSV, respectively, for 30 days. The results of this study revealed that PEMB leads to a significant increase in thiobarbituric acid reactive substance (TBARS) levels and a significant decrease in glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD) activities, and glutathione (GSH) levels in the liver and brain tissues. The decreased SOD, CAT, GPx activities, and GSH levels increased significantly following RSV treatment in Group 4. The PEMB treatment showed histopathological alterations associated with strong positive cysteinyl aspartic acid-protease-3 (caspase-3) immunoreactivity, while RSV treatment reduced both the expression of caspase-3 protein and the histopathological changes. RSV administration prevents the biochemical, immunological, and histological alterations induced by PEMB. It can be suggested that the lower caspase-3 immunoreactivity in the PEMB + RSV group than in the PEMB group led to an inhibition of RSV on apoptosis.
Keywords: hepatotoxicity; neurotoxicity; oxidative stress; pembrolizumab; resveratrol